The Institutional Basis of Gender Inequality - Boris Branisa; Maria Ziegler; Stephan Klasen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
In this paper we construct the Social Institutions and Gender Index (SIGI) and its five subindices Family code, Civil liberties, Physical integrity, Son Preference and Ownership rights using variables of the OECD Gender, Institutions and Development database. Instead of measuring gender inequality in education, health, economic or political participation, these indices allow a new perspective on gender issues in developing countries. The SIGI and the subindices measure long-lasting social institutions which are mirrored by societal practices and legal norms that frame gender-relevant meanings and form the basis of gender roles. The subindices measure each one dimension of the concept and the SIGI combines the subindices into a multidimensional index of deprivation of women caused by social institutions. Methodologically, the SIGI is inspired by the Foster-Greer-Thorbecke poverty measures. It offers a new way of aggregating gender inequality in several dimensions, penalizing high inequality in each dimension and allowing only for partial compensation between dimensions. The SIGI and the subindices are useful tools to identify countries and dimensions of social institutions that deserve attention. Empirical results confirm that the SIGI provides additional information to that of other well-known gender-related indices.
Keywords: D63; I39; J16; 330; SIGI; Composite index; Gender inequality; Social institutions; OECD-GID database